Evaluation of biscuits obtained from novel composite flour containing Maiorca malt flour - Benanti, Alessia; Rabie Ashkezary, Mansour; Gugino, Ignazio Maria; Canale, Michele; Yeganehzad, Samira; Todaro, Aldo (Italian Journal of Food Science, 2023)
The aim of this study was to investigate a novel composite flour containing one of the old Sicilian wheat landraces called Maiorca and the resultant biscuits. In this study, the effect of replacing soft wheat flour with Maiorca malt flour and commercial malt flour at different percentages (5, 10, and 15%) on the color intensity, formation of acrylamide, and descriptive sensory analysis was evaluated. Sensory analysis revealed that the biscuit sample containing 5% Maiorca malt flour was most appreciated by panelists. Eventually, data analysis revealed that Maiorca malt flour had great potential to be used as a part of biscuit ingredients.